2015
DOI: 10.1016/j.ijrobp.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Clinical Impact of Approximations in Analytical Dose Calculations for Proton Therapy

Abstract: Purpose To assess the impact of approximations in current analytical dose calculation methods (ADCs) on tumor control probability (TCP) in proton therapy. Methods Dose distributions planned with ADC were compared to delivered dose distributions (as determined by Monte Carlo simulations). A total of 50 patients were investigated in this analysis with 10 patients per site for 5 treatment sites (head-and-neck, lung, breast, prostate, liver). Differences were evaluated using dosimetric indices based on a dose-vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 30 publications
8
87
0
Order By: Relevance
“…The magnitude of improvement observed with Monte Carlo algorithms for proton therapy, as indicated in our results, is larger than for photon therapy, making this issue even more important for proton therapy. This study is also largely consistent with the results of Schuemann et al who compared their analytic algorithm with Monte Carlo for several disease sites (16). They also observed discrepancies: the analytic algorithm predicted higher dose to the target volumes than did the Monte Carlo algorithm, although in the lung, their dose difference was only as large as 5%.…”
Section: Discussionsupporting
confidence: 91%
“…The magnitude of improvement observed with Monte Carlo algorithms for proton therapy, as indicated in our results, is larger than for photon therapy, making this issue even more important for proton therapy. This study is also largely consistent with the results of Schuemann et al who compared their analytic algorithm with Monte Carlo for several disease sites (16). They also observed discrepancies: the analytic algorithm predicted higher dose to the target volumes than did the Monte Carlo algorithm, although in the lung, their dose difference was only as large as 5%.…”
Section: Discussionsupporting
confidence: 91%
“…It has been demonstrated that, relative to Monte Carlo (MC) simulations, proton pencil beam algorithms typically over-estimate the mean dose delivered to deep-seated targets such as the prostate by approximately 2% whilst under-estimating the scattered dose to normal tissues [10]. Consequently, in this study proton plan-specific scaling factors were applied to the MC dose distributions so that the dose received by 90% of a patient's CTV volume matched that for their IMRT plan.…”
Section: Methodsmentioning
confidence: 99%
“…The doses and the three-dimensional LET d distributions were calculated using the TOPAS Monte Carlo system [30], based on the prescribed delivery parameters from the treatment planning system [31].…”
Section: Patient Cohort Dose Calculation and Model Parametersmentioning
confidence: 99%